2016
DOI: 10.7554/elife.17578.016
|View full text |Cite
|
Sign up to set email alerts
|

Author response: The amyloid-beta forming tripeptide cleavage mechanism of γ-secretase

Abstract: g-secretase is responsible for the proteolysis of amyloid precursor protein (APP) into short, aggregation-prone amyloid-beta (Ab) peptides, which are centrally implicated in the pathogenesis of Alzheimer's disease (AD). Despite considerable interest in developing g-secretase targeting therapeutics for the treatment of AD, the precise mechanism by which g-secretase produces Ab has remained elusive. Herein, we demonstrate that g-secretase catalysis is driven by the stabilization of an enzyme-substrate scission c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
6
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
3
2

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(6 citation statements)
references
References 0 publications
0
6
0
Order By: Relevance
“…Photoprobes TSA-Bpa-Bt (left) and HPI-Bpa-Bt (right) covalently label presenilin-1 (PS1) N-terminal fragment (NTF) at the active site and docking site, respectively. (a) TSA (17) but not HPI (2) decreased the labelling of PS1 NTF by the TSA photoprobe. (b) HPI (2) but not TSA (17) decreased the labelling PS1 NTF by the HPI photoprobe.…”
Section: Supplementary Materialsmentioning
confidence: 99%
See 3 more Smart Citations
“…Photoprobes TSA-Bpa-Bt (left) and HPI-Bpa-Bt (right) covalently label presenilin-1 (PS1) N-terminal fragment (NTF) at the active site and docking site, respectively. (a) TSA (17) but not HPI (2) decreased the labelling of PS1 NTF by the TSA photoprobe. (b) HPI (2) but not TSA (17) decreased the labelling PS1 NTF by the HPI photoprobe.…”
Section: Supplementary Materialsmentioning
confidence: 99%
“…(a) TSA (17) but not HPI (2) decreased the labelling of PS1 NTF by the TSA photoprobe. (b) HPI (2) but not TSA (17) decreased the labelling PS1 NTF by the HPI photoprobe. (c, d).…”
Section: Supplementary Materialsmentioning
confidence: 99%
See 2 more Smart Citations
“…[10][11][12][13] We have also reported helical peptide inhibitors (HPIs) that interact with a substrate docking exosite distinct from but proximal to the active site. [14][15] We recently demonstrated that substrate TMD is sufficient for highaffinity binding (K m < 100 nM) 16 and therefore sought peptide-based inhibitors that would mimic the entire TMD and interact with both the docking site and the active site. Specifically, we worked to couple an HPI to a TSA through a variable linker (Fig.…”
mentioning
confidence: 99%